2013
DOI: 10.1177/0194599812473412
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain after Adenotonsillectomy Is More Common in Young Children

Abstract: Similar to previous studies, children had weight gain after TA. In this analysis, younger age (≤ 6 years) was a significant predictor of postoperative weight gain. Future research should prospectively evaluate the association between weight gain and demographic factors in children undergoing TA, with special attention to the relationship with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
41
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 27 publications
5
41
1
Order By: Relevance
“…Although the night breath restriction factors lifted, the growth promoter (IGF-1) can get a significant increase, which leads to height and weight gain, consistent with previous studies reporting catch-up growth after T&A. 22,24,25 A difference remains, however, between patients with OSAS and their twin brothers or sisters, although the results of PSG indicated no sleep problems after surgical intervention. Some papers had indicated that T&A is useful for preschool children.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although the night breath restriction factors lifted, the growth promoter (IGF-1) can get a significant increase, which leads to height and weight gain, consistent with previous studies reporting catch-up growth after T&A. 22,24,25 A difference remains, however, between patients with OSAS and their twin brothers or sisters, although the results of PSG indicated no sleep problems after surgical intervention. Some papers had indicated that T&A is useful for preschool children.…”
Section: Discussionsupporting
confidence: 86%
“…[22][23][24][25] Most conclusions, however, were drawn from pre-and postoperative results, and furthermore, the control groups were normal children. The growth pattern and rate of children differ by ages, family status, and the parents' genetic predisposition.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may suggest that weight gained after adenotonsillectomy is more fat than lean body mass. However, as in multiple other studies, 9,10,17 we did not observe an increase in the overall rate of obesity before and after surgery. Although we found that most of the weight gain is seen in the 4½ to 6 months after adenotonsillectomy, it does not plateau until 1 year after surgery.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with other studies that showed rapid weight gain in postadenotonsillectomy. [1011]…”
Section: Discussionmentioning
confidence: 99%